Clinical characteristics and prognosis associated with multiple primary malignant tumors in non-Hodgkin lymphoma patients. Issue 6 (December 2019) - Jiang, Yanan; Miao, Zhaoyi; Wang, Jinhuan; Chen, Jing; Lv, Yangyang; Xing, Donghui; Wang, Xiaofang; Wang, Yafei; Cao, Zeng; Zhao, Zhigang
Objective: Patients with non-Hodgkin lymphoma (NHL) occasionally present with multiple primary malignant tumors (MPMTs). This study aimed to determine the clinical characteristics, survival, and risk factors of these patients. Methods: The median follow-up of 92 patients was 13.5 months (range 0.3–72). Overall, 21 patients had synchronous MPMTs and 71 had metachronous MPMTs. We classified patients in the latter group into metachronous first group (n=27) and metachronous second group (n=44). Results: Diffuse large B-cell lymphoma was the most frequent histologic lymphoma type. The digestive system was the commonest site affected by the solid cancer. The 1- and 2-year survival rates were 86.5% and 70.5%, respectively. The overall survival (OS) rates were 67.9% and 36.2% at 2 and 3 years, respectively, in the metachronous first group; 73.8% and 73.8%, respectively, in the metachronous second group; and 68.1% and 56.7%, respectively, in the synchronous tumor group. There was no difference in the survival rate among the 3 groups before 2 years, but after 2 years, a shorter OS rate was observed in the metachronous first group than in the metachronous second group and synchronous tumor group. For all patients, age >60 years, male sex, and ⩾3 involved nodal sites were considered independent prognostic factors associated with survival. Conclusions: OS time was shorter in patients with NHL who developed a second tumor than in those who were diagnosed with solid cancer synchronously and second neoplasm after previous solid tumors. Long-term follow-up and effective treatment should be provided to these patients.